Psychological determinants of 3R behavior: A secondary data analysis from Bappenas within the Framework of SDGs 12 in Indonesia - Renanda Pratama Herdianto (Sustainable Urban Development and Environmental Impact Journal, 2026)
Background: Urban areas in Indonesia face mounting waste challenges driven by rapid population growth and unsustainable consumption. To advance Sustainable Development Goals (SDGs) 12 on responsible consumption and production, this study investigates the psychological determinants of 3R (Reduce, Reuse, Recycle) behavior using secondary data from the Ministry of National Development Planning (Bappenas). Methods: Employing a descriptive–correlational design, the research operationalizes environmental awareness, pro-environmental attitudes, perceived behavioral control, and social norms through macro-level proxy indicators. The study utilizes a purposive sampling of urban datasets (2021–2022), where psychological constructs are proxied by infrastructure density, participation rates, and local policy metrics, subsequently analyzed through multiple regression using R and SPSS software to ensure statistical rigor. Findings: Regression analysis reveals that pro-environmental attitudes and perceived behavioral control are the strongest predictors of 3R engagement, while social norms play a reinforcing role. These findings align with the Theory of Planned Behavior and Value Belief Norm Theory. Collectively, these psychological factors explain approximately 64% of the variance in 3R behavior, confirming that both individual motivations and collective social pressures are critical drivers of environmentally responsible action in the Indonesian context. Conclusion: These results underscore the importance of embedding behavioral perspectives into sustainability strategies. By demonstrating how psychological factors shape waste-related actions, the study highlights the need for policies that go beyond infrastructure focusing instead on motivation, capability, and social reinforcement to foster lasting 3R engagement. Novelty/Originality of this article: This study offers one of the first empirical analyses using national level data to explain psychological drivers of sustainable waste behavior in Indonesia, providing a foundation for targeted strategies that integrate behavioral insights into SDGs 12 implementation.